Cytogenetic analysis of Phyllomedusa distincta Lutz, 1950 (2n = 2x = 26), P. tetraploidea Pombal and Haddad, 1992 (2n = 4x = 52), and their natural triploid hybrids (2n = 3x = 39) (Anura, Hylidae, Phyllomedusinae) - Gruber, Simone Lilian [UNESP]; Silva, Ana Paula Zampieri [UNESP]; Haddad, Célio Fernando Baptista [UNESP]; Kasahara, Sanae [UNESP] (Springer Nature, 2013)
Background: Natural polyploidy has played an important role during the speciation and evolution of vertebrates, including anurans, with more than 55 described cases. The species of the Phyllomedusa burmeisteri group are mostly characterized by having 26 chromosomes, but a karyotype with 52 chromosomes was described in P. tetraploidea. This species was found in sintopy with P. distincta in two localities of São Paulo State (Brazil), where triploid animals also occur, as consequence of natural hybridisation. We analyse the chromosomes of P. distincta, P. tetraploidea, and their triploid hybrids, to enlighten the origin of polyploidy and to obtain some evidence on diploidisation of tetraploid karyotype.Results: Phyllomedusa distincta was 2n = 2x = 26, whereas P. tetraploidea was 2n = 4x = 52, and the hybrid individuals was 2n = 3x = 39. In meiotic phases, bivalents were observed in the diploid males, whereas both bivalents and tetravalents were observed in the tetraploid males. Univalents, bivalents or trivalents; metaphase II cells carrying variable number of chromosomes; and spermatids were detected in the testis preparations of the triploid males, indicating that the triploids were not completely sterile. In natural and experimental conditions, the triploids cross with the parental species, producing abnormal egg clutches and tadpoles with malformations. The embryos and tadpoles exhibited intraindividual karyotype variability and all of the metaphases contained abnormal constitutions. Multiple NORs, detected by Ag-impregnation and FISH with an rDNA probe, were observed on chromosome 1 in the three karyotypic forms; and, additionally, on chromosome 9 in the diploids, mostly on chromosome 8 in the tetraploids, and on both chromosome 8 and 9 in the triploids. Nevertheless, NOR-bearing chromosome 9 was detected in the tetraploids, and chromosome 9 carried active or inactive NORs in the triploids. C-banding, base-specific fluorochrome stainings with CMA3 and DAPI, FISH with a telomeric probe, and BrdU incorporation in DNA showed nearly equivalent patterns in the karyotypes of P. distincta, P. tetraploidea, and the triploid hybrids.Conclusions: All the used cytogenetic techniques have provided strong evidence that the process of diploidisation, an essential step for stabilising the selective advantages produced by polyploidisation, is under way in distinct quartets of the tetraploid karyotype. © 2013 Gruber et al.; licensee BioMed Central Ltd.
Keywords: Chromosome banding; Diploidisation; FISH; Molecular cytogenetics; Polyploidy; cell differentiation; chromosome 1; chromosome 11; chromosome 13; chromosome 2; chromosome 3; chromosome 6; chromosome 7; chromosome 8; chromosome 9; chromosome analysis; chromosome structure; embryo; female; karyotype; male; metaphase; nonhuman; Phyllomedusa; Phyllomedusa distincta; Phyllomedusa tetraploidea; silver impregnation; spermatid; tetraploidy; triploidy; Animalia; Anura; Hylidae; Phyllomedusa burmeisteri; Phyllomedusinae; Vertebrata